Decentralisation, clientelism and social protection programmes: a study of India's MGNREGA. (2nd October 2018) - Maiorano, Diego; Das, Upasak; Masiero, Silvia
Abstract: Does decentralisation promote clientelism? If yes, through which mechanisms? We answer these questions through an analysis of India's (and the world's) largest workfare programme, the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), in two Indian states: Rajasthan and Andhra Pradesh (AP). The two states adopted radically different implementation models: Rajasthan's decentralised one stands in contrast with Andhra Pradesh's centralised and bureaucracy-led model. Using a mixed method approach, we find that in both states local implementers have incentives to distribute MGNREGA work in a clientelistic fashion. However, in Rajasthan, these incentives are stronger, because of the decentralised implementation model. Accordingly, our quantitative evidence shows that clientelism is more serious a problem in Rajasthan than in AP.